Factors Influencing Utilization of Health and Wellness Centers (HWCs) in Odisha: A Mixed Method Study from Beneficiaries' Perspective - Amitosh Dandsena; Paramjot Panda; Jyotirmayee Rath; Akash Kumar Panigrahi (Wolters Kluwer Medknow Publications, 2023)
Background: According to the National Family Health Survey-5 report, Odisha's population with hypertension has a 5% noncommunicable disease (NCD) burden, and only 40% of people in Odisha use primary health-care facilities to treat their NCDs, despite the Government of India having developed these facilities through the health and wellness centre (HWC) initiative. Aim and Objective: The aim of the study is to evaluate the utilization of Health and Wellness Centers (HWCs) in Odisha from the perspective of beneficiaries, and to identify factors influencing their low utilization, using a mixed-method approach. Materials and Methods: The study utilized a mixed-method approach, with a sample size of 400 participants. Quantitative data were collected through structured interviews, analysed using frequency and percentage calculations, and assessed for associations using logistic regression. Qualitative data were obtained via in-depth interviews, and thematic analysis was applied to identify major themes and subthemes related to HWC utilization and beneficiaries' perceptions. Ethical clearance and informed consent were obtained before data collection. Results: In this study with 400 participants, only 31% utilized Health and Wellness Centers (HWCs) in Odisha. Factors associated with utilization included no formal education, proximity to HWCs within 2 km, low household income, experiencing general illness, and availing allopathic treatment which is statically significant with p<0.05. In-depth interviews revealed positive influences for utilization, such as nearby distance to HWCs, free testing and medicine, and positive expectations from government hospitals. Barriers to utilization included negative experiences, transportation challenges, lack of awareness, and poor beliefs or perceptions about HWCs. Conclusion: The study on Health and Wellness Centre (HWC) utilization in Odisha conclude that only 31% of beneficiaries access these facilities. Education, distance, and household income influence utilization. Proximity, free services, and awareness campaigns can improve utilization and foster preventive healthcare. The study recommends the policy makers to take action to bridge gaps and unleash the true potential of HWCs, creating a healthier future for Odisha.